1993
DOI: 10.1017/s0950268800050901
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxins and toxic-shock syndrome toxin-1 in non-enteric staphylococcal disease

Abstract: SUMMARYOver the 7 years 1985-91, 997 strains of Staphylococcus aureus from 962 patients with diseases other than food poisoning have been tested for the production of enterotoxins and toxic shock syndrome toxin-I (TSST-1) and phage typed. In all, 128 cases could be classified as confirmed or probable toxic shock syndrome (TSS) but a further 199 cases were classified as possible or unconfirmed TSS. In 219 cases, an alternative diagnosis could be supported and 45 cases were classified as sudden infant death synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
0
7
0
3
Order By: Relevance
“…In this study, we found that the prevalence of positive rates of SEA/SEB‐specific antibodies was 33.6% in all patients with AD. It is likely that the positive rate of SEB‐specific IgE antibodies was higher than that of SEA‐specific IgE antibodies because SEB is associated with local infections, while SEA is often encountered in patients with toxic shock syndrome 14 . The positive rate of SEA/SEB‐specific antibodies in the patients suffering from severe AD was higher than in those with mild AD.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, we found that the prevalence of positive rates of SEA/SEB‐specific antibodies was 33.6% in all patients with AD. It is likely that the positive rate of SEB‐specific IgE antibodies was higher than that of SEA‐specific IgE antibodies because SEB is associated with local infections, while SEA is often encountered in patients with toxic shock syndrome 14 . The positive rate of SEA/SEB‐specific antibodies in the patients suffering from severe AD was higher than in those with mild AD.…”
Section: Discussionmentioning
confidence: 95%
“…It manifests with a scarlet fever-like rash and has been tentatively described in some reports as a milder form of SSSS caused by the systemic diffusion of exfoliative toxins [2][3][4][5][12][13][14][15]. In contrast to these reports, a few studies have shown that TSST-1 or enterotoxins, or both, are the major toxins involved in SSF [6,7,16,17]. Jarraud et al [6] and Lina et al [7] analyzed 20 strains of S. aureus isolated from patients with SSF and found that 8 isolates produced enterotoxins only, 7 isolates produced TSST-1 only, 1 isolate produced both ETA and ETB, and 4 isolates produced both TSST-1 and enterotoxins.…”
mentioning
confidence: 99%
“…Verschiedene Studien konnten zeigen, daß zwischen 25%-40% der untersuchten 5. az/7-<?2<,y-Isolate mindestens eines der drei Superantigene-TSST-1, Enterotoxin B oder Enterotoxin C bildeten [11][12][13][14][15][16][17][18]. Damit wird deutlich, daß immerhin jedes vierte S. aureus-Isolat unter bestimmten Bedingungen über eine Superantigenbildung ein TSS auslösen könnte.…”
Section: Diskussionunclassified
“…Dies wiederum impliziert, daß es neben Superantigenen auch alternative Ursachen bzw. Mechanismen für einen grampositiven Schock geben muß [11][12][13][14][15][16][17][18].…”
unclassified